Penguatan Kolaborasi Guru dan Orang Tua untuk Mendukung Masa Pengenalan Lingkungan Prasekolah - Nur, Maulida; Rohmiyati, Yuli; Risna, Inten; Apriyanti, Ranti; Safaat Aeni, Ira; Oktavianti, Oppyta; Fadillah, Nurul; Pungki, Anjela; Sanuri, Sanuri; Ikhtivaya, Sri (Universitas Pahlawan Tuanku Tambusai, 2025)
The transition period is a crucial time for children, during which they are required to adapt to a new environment and various changes. Many children feel anxious, afraid, or hesitant to be separated from their parents. The role of parents and teachers is vital in helping children adapt during this period so that they are ready for school. The DPL KKM 70 UNIBA group conducted community service activities coinciding with the beginning of the new school year in the form of parenting sessions, featuring speakers from PGPAUD UNIBA lecturers, using a socialization method. This activity aimed to encourage parents to prepare for their child's transition period, recognize their needs, and promote active parental involvement in optimizing child growth and development through collaboration between teachers and parents. The results showed an increase in parental understanding before and after the socialization. If you want, I can also help make it more concise or formal.